Circular References and Logic

Manoj Kasichainula manojk+fork@io.com
Sat, 20 Apr 2002 19:14:59 -0700


> >#1: Statement #2 is true.
> >#2: Statement #1 is false.
> >
> >Assume statement #1 is true. Then statement #2 is true. But, statement #2
> >[...]
> >These two statements contradict each other, and are neither true nor false.

This becomes easy if you just drop the binary notion of true and false
and use fuzzy logic. Assume

1 = completely true
0 = completely false
a = truth value of statement #1
b = truth value of statement #2

then, the statements can be written as (if I remember my fuzzy logic
correctly):

a = b
b = 1 - a

Which gets solved pretty easily as a = b = 0.5.

So both statements are kind of true. No problem. :)